IMPACT OF PATIENT SAFETY PROTOCOLS ON HOSPITAL READMISSION RATES AND HEALTHCARE COSTS. A SYSTEMATIC REVIEW (Journal of Medical & Health Sciences Review, 2025)
Background: This paper examines the impact of patient safety protocols on hospital readmission rates and healthcare costs. Patient safety protocols have been implemented to enhance healthcare quality, minimize errors, and reduce adverse events, but their influence on readmission rates and costs remains understudied. This research aims to provide a systematic review of peer-reviewed literature to assess the effectiveness of these protocols in improving patient outcomes and reducing healthcare costs.Methods: A systematic review approach was used to analyze studies published from 2019 to the present. Databases such as PubMed, Scopus, Google Scholar, ScienceDirect, and Web of Science were searched using specific keywords related to patient safety protocols, readmissions, and healthcare costs. Studies included in the review were clinical trials, observational studies, and systematic reviews, while case reports, editorials, and non-peer-reviewed publications were excluded. The quality of studies was assessed using established evaluation tools such as AMSTAR, Cochrane Risk of Bias Tool, and NOS.Results: The analysis reveals that patient safety protocols significantly impact hospital readmission rates and healthcare costs. A majority of studies report a decrease in readmission rates following the implementation of safety measures such as hand hygiene, infection control, and medication safety protocols. Additionally, these protocols are associated with reduced healthcare costs due to fewer readmissions and fewer adverse events. However, challenges such as adherence issues, training gaps, and inconsistent implementation remain significant barriers to their effectiveness.Conclusion: Patient safety protocols are highly effective in reducing hospital readmissions and healthcare costs. While the protocols' implementation demonstrates clear benefits, ensuring consistent application and overcoming challenges related to adherence and staff training are essential for maximizing their impact. Future research should focus on identifying strategies to address these challenges and further explore the long-term effects of patient safety protocols on healthcare outcomes and costs.